Sedentary behavior patterns and bone health among overweight/obesity older women: a cross-sectional study - He, Yixian; Du, Litao; Li, Qingqian; Ren, Xiaoyu; Chen, Si; Pan, Yang (Frontiers in Medicine, 2024)
Background: Recent studies have indicated an association between sedentary behavior(SB), particularly patterns of SB, and bone health. However, it remains uncertain how different patterns of SB in overweight/obesity older women impact their bone health. This study aimed to investigate the association between objectively measured SB patterns and bone health in Chinese communitydwelling overweight/obesity older women.Methods: Cross-sectional data were obtained from a baseline survey of Physical Activity and Health in Older Women Study. Quantitative ultrasound was used to measure speed of sound(SOS), broadband ultrasound attenuation(BUA), bone quality index(BQI) and T value to evaluate bone health. SB patterns were measured using triaxial accelerometers, including sedentary time in SB bouts of ≥10, 30 and 60 min, number of SB bouts ≥10, 30 and 60 min. Multiple linear regression was used to examine the associations of different SB patterns with bone health.Results: After adjusting for confounders, sedentary time in SB bouts ≥60 min, number of SB bouts ≥60 min were significantly associated with bone health, with a lower SOS(β=-2.75, 95% confidence interval(CI): -4.96 to -0.53, P=0.015), BUA(β=-1.20, 95%CI: -2.14 to -0.26, P=0.013), BQI(β=-1.56, 95%CI: -2.63 to -0.49, P=0.004), T value(β=-0.08, 95%CI: -0.14 to -0.03, P=0.004) per 60 min increase of sedentary time in SB bouts ≥60 min, and a lower SOS(β=-3.97, 95%CI: -7.54 to -0.40, P=0.029), BUA(β=-1.80, 95%CI: -3.44 to -0.16, P=0.031), BQI(β=-2.28, 95%CI: -4.08 to -0.47, P=0.014) and T value(β=-0.12, 95%CI: -0.22 to -0.03, P=0.013) per bout increase of SB bouts ≥60 min, respectively.Conclusions: Limiting the duration of prolonged sedentary bouts and minimizing the occurrence of number of SB bouts ≥60 min could be essential in bone health management, especially for those older people who are overweight/obesity.